"Using Crowd-Sourced Data to Explore Police-Related-Deaths in the United States (2000–2017): The Case of Fatal Encounters". (7th May 2019) - Finch, Brian Karl; Beck, Audrey; Burghart, D. Brian; Johnson, Richard; Klinger, David; Thomas, Kyla
Objectives: We evaluated the Fatal Encounters (FE) database as an open-source surveillance system for tracking police-related deaths (PRDs). Methods: We compared the coverage of FE data to several known government sources of police-related deaths and police homicide data. We also replicated incident selection from a recent review of the National Violent Death Reporting System. Results: FE collected data on n = 23, 578 PRDs from 2000–2017. A pilot study and ongoing data integration suggest greater coverage than extant data sets. Advantages of the FE data include circumstance of death specificity, incident geo-locations, identification of involved police-agencies, and near immediate availability of data. Disadvantages include a high rate of missingness for decedent race/ethnicity, potentially higher rates of missing incidents in older data, and the exclusion of more comprehensive police use-of-force and nonlethal use-of-force data—a critique applicable to all extant data sets. Conclusions: FE is the largest collection of PRDs in the United States and remains as the most likely source for historical trend comparisons and police-department level analyses of the causes of PRDs.